The Significance of Accounts Receivable Turnover, Debt to Equity Ratio, Current Ratio to The Probability of Manufacturing Companies - Arni Elly Agustina Manullang; Delima Togatorop; Priscilia Rani Devita Purba; Elfriede Aturma Yanti Manik; Enda Noviyanti Simorangkir; Rolina Kristiani Lase (International Journal of Social Science and Business, 2020)
The very rapid economic development is one aspect that affects the progress of a country, both developed and developing countries. Including in a developing country of Indonesia, with a rapid economic development, it is very costly or quite large to advance the Indonesian state. This study aims to analyze the influence of accounts receivable turnover, debt to equity ratio, current ratio to profitability (Return on Asset) in basic industrial and chemical manufacturing companies listed on the IDX in 2016-2018. The research method used in this research is descriptive method and multiple linear analysis method. The data used are annual financial reports published on the Indonesia Stock Exchange which provide data on financial reports. The variables related to this research are accounts receivable turnover, debt to equity ratio and current ratio. The data source used is secondary data. The population of this study were 66 companies with a sample of 36 companies. The results of this study indicate that accounts receivable turnover has no and insignificant effect on profitability (Return on Asset), debt to equity ratio has no and insignificant effect on profitability (Return on Asset), current ratio has significant and significant effect on profitability (Return on Asset).